Effects of Indoor Endocrine-Disrupting Chemicals on Childhood Rhinitis - Paciência, I (2020)
Endocrine-disrupting chemicals (EDCs) are ubiquitous in our environment and pose a threat not only to the indoor environment but also to public health. Despite the widespread presence of these chemicals indoors, our understanding of the extent and the health effects of exposure is limited by insufficient data on exposure patterns and the action of EDCs over a person’s lifespan. Previous evidence suggested that both individual and coexposure to low concentrations of EDCs in classrooms were associated with an increased risk of asthma, obesity, and an increased prevalence of nasal obstruction in the previous 3 months among children. Furthermore, we found that exposure to EDCs was also associated with changes in the autonomic nervous system, specifically parasympathetic dysautonomia, thus suggesting that EDCs may increase parasympathetic activity, resulting in a subsequent increase in the risk of asthma, respiratory symptoms, and obesity. In addition to the observed effect of EDCs on nasal obstruction, ie, one of the defining symptoms of rhinitis, asthma frequently coexists with allergic rhinitis (AR), which is a risk factor for the development of asthma. However, no studies have yet addressed the effects of exposure to EDCs on rhinitis. Therefore, we aimed to assess the effect of indoor individual or combined exposure to EDCs on rhinitis in schoolchildren.